2011
DOI: 10.1159/000327529
|View full text |Cite
|
Sign up to set email alerts
|

Tributyltin Alters Osteocalcin, Matrix Metalloproteinase 20 and Dentin Sialophosphoprotein Gene Expression in Mineralizing Mouse Embryonic Tooth in vitro

Abstract: We showed in a previous in vitro study that tributyltin (TBT) arrests dentin mineralization and enamel formation in developing mouse tooth. The present aim was to investigate the effect of TBT on the expression of genes associated with mineralization of dental hard tissues. Embryonic day 18 mouse mandibular first molars were cultured for 3, 5 or 7 days and exposed to 1.0 µM TBT and studied by real-time quantitative polymerase chain reaction (RT-QPCR) for the expressions of osteocalcin (Ocn), alkaline phosphata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…Exposure of RA-treated cell aggregates to BMP-4 triggered their odontoblastic differentiation as measured by a coordinate increase in the expression of a specific set of mineralization-regulating genes. Several non-collagenous proteins important in mineralization are expressed in both bone and dentin but at different levels (32)(33)(34). The ECM protein DSPP is thought to be more tooth-specific and is strongly expressed by odontoblasts (32,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure of RA-treated cell aggregates to BMP-4 triggered their odontoblastic differentiation as measured by a coordinate increase in the expression of a specific set of mineralization-regulating genes. Several non-collagenous proteins important in mineralization are expressed in both bone and dentin but at different levels (32)(33)(34). The ECM protein DSPP is thought to be more tooth-specific and is strongly expressed by odontoblasts (32,35).…”
Section: Discussionmentioning
confidence: 99%
“…Because both bone and teeth express these markers at variable levels depending on their stage of differentiation, this group of protein indicators has limited use in discriminating between osteoblast and odontoblast lineages. However, MMP-20 (enamelysin) is thought to be highly tooth-specific, and its expression has been found in epithelial ameloblasts and mesenchymal odontoblasts (34,35). Analysis revealed that both cultured ameloblastic and odontoblastic cells, but not osteoblastic cells, expressed high levels of MMP-20 protein (39).…”
Section: Discussionmentioning
confidence: 99%
“…Bone is an endocrine target tissue highly sensitive to numerous ED [ 189 ]. Data from in vitro and in vivo studies indicate that tributyltin chloride (TBT) can disrupt the process of bone deposition and remodeling [ 190 , 191 , 192 ]. Similarly, TBT seems to stimulate adipogenesis and ectopic adipocyte formation through PPAR-γ activation [ 193 , 194 ].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Dentinogenesis imperfecta, a hereditary tooth defect, has been observed in humans with a mutant DSPP gene (Kim et al , 2005) and in p20CEBPB transgenic mice (Savage et al , 2006). Of further note, earlier studies have suggested an influence of IGF1 on dental maturation (Campbell et al , 2009), a preventing effect of RUNX2 upon development of succedaneous tooth organs (D’Souza et al , 1999), and an odontogenic relevance of BGLAP (Salmela et al , 2012). As mentioned earlier, activity of IGF1, RUNX2 and BGLAP was subject to CEBPB regulation (McCarthy et al , 2000; Gutierrez et al , 2002; Wiper‐Bergeron et al , 2007).…”
Section: Introductionmentioning
confidence: 99%